Legal Protection for Search and Rescue Officers (Civil Servants) in the Implementation of Search and Rescue Operations - Hakim Fajrin; Lusia Sulastri (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Search and Rescue (SAR) officers who serve as Civil Servants (ASN) play a strategic role in saving human lives during rescue operations. However, this responsibility exposes them to high occupational risks, including severe injury and death, which necessitates strong and comprehensive legal protection. This study aims to analyze the legal protection framework for SAR personnel within Indonesia’s national regulations and identify challenges in its implementation. Using a normative juridical approach, the research examines Law Number 29 of 2014 concerning Search and Rescue, the Head of BASARNAS Regulation Number 1 of 2025, and several empirical cases highlighting the limited legal safeguards for rescuers. The findings indicate that, despite existing regulations on liability and compensation mechanisms, implementation remains suboptimal due to overlapping policies, weak inter-agency coordination, and limited compensation funding. Comparative analysis with international standards further reveals that legal protection for rescuers must include occupational safety, fair compensation rights, and legal certainty for the families of victims. Therefore, a more assertive and responsive legal policy framework is required to ensure justice, legal certainty, and proper recognition for ASN officers serving at the humanitarian front line.